Le rôle des syndicats québécois en matière d’accommodement des personnes handicapées - Annick Desjardins (Perspectives Interdisciplinaires sur le Travail et la Santé)
The obligation to accommodate workers with disabilities, due to significant developments in case law, has gained importance in Québec, such that the role of trade unions has evolved in the context of these changes. Unions are faced with a change in their role that is imposed, that provides them with powerful tools to demand measures to facilitate the integration and retention of employees with disabilities, but that also creates a situation where union representatives have to arbitrate conflicting interests among their members. This text explains the role of unions in this new dynamic in labour relations, and discusses the limitations in trade union action with respect to the duty to accommodate persons with disabilities.